1975
DOI: 10.1007/bf00432306
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary alveolar proteinosis and histoplasmosis

Abstract: Pulmonary alveolar proteinosis (PAP), in addition to acute generalized histoplasmosis, was found at autopsy of three adult males, 23, 51, and 52 years of age. All three patients became ill in the same region of Venezuela, south of Lake Maracaibo, an area considered highly endemic for histoplasmosis. The PAP may be due to an environmental factor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
15
0
1

Year Published

1998
1998
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(16 citation statements)
references
References 3 publications
0
15
0
1
Order By: Relevance
“…Indeed, reduced cell adhesion, phagocytosis, pathogen killing, mannose-and Toll-like receptor expression, and LPS-or peptidoglycan-stimulated TNFα release were observed in alveolar macrophages and neutrophils from GM-CSF deficient mice and PAP patients [31,35]. Accordingly, PAP patients developed respiratory and extrapulmonary infections with opportunistic pathogens such as nontuberculous mycobacteria, Histoplasma, Cryptococcus, Nocardia or fungi [35][36][37][38][39][40]. Notably, this spectrum of infections appears very similar to the phenotype associated with the presence of neutralizing anti-IFNγ AAbs [6].…”
Section: Anti-gm-csf Autoantibodiesmentioning
confidence: 95%
“…Indeed, reduced cell adhesion, phagocytosis, pathogen killing, mannose-and Toll-like receptor expression, and LPS-or peptidoglycan-stimulated TNFα release were observed in alveolar macrophages and neutrophils from GM-CSF deficient mice and PAP patients [31,35]. Accordingly, PAP patients developed respiratory and extrapulmonary infections with opportunistic pathogens such as nontuberculous mycobacteria, Histoplasma, Cryptococcus, Nocardia or fungi [35][36][37][38][39][40]. Notably, this spectrum of infections appears very similar to the phenotype associated with the presence of neutralizing anti-IFNγ AAbs [6].…”
Section: Anti-gm-csf Autoantibodiesmentioning
confidence: 95%
“…103,104 The crazy-paving pattern is not pathognomonic of pulmonary alveolar proteinosis, and occurs in other infectious or non-infectious conditions. [104][105][106][107][108][109][110][111][112][113][114] The subacute or chronic clinical course, absence of architectural distortion, smooth 78 Cryptococcus neoformans 79,80 Mycobacterium tuberculosis [81][82][83][84] Mycobacterium avium-intracellulare 85,86 inter-lobular septal thickening, geographical distribution, and discordance between the clinical and radiological features help differentiate pulmonary alveolar proteinosis from other causes of crazy paving. In a study of 42 patients, Ishii et al 115 reported differences in the pattern and distribution of ground-glass opacity on high-resolution CT, which help to differentiate secondary from autoimmune pulmonary alveolar proteinosis.…”
Section: High-resolution Computed Tomographymentioning
confidence: 99%
“…[5][6][7], Mycobacterium sp. [8][9][10][11][12][13], Cryptococcus neoformans [14], Histoplasma capsulatum [15], Pneumocystis carinii [16], and virus [17]. Rarely, cases of PAP may be associated with Mycobacterium tuberculosis [10,13].…”
mentioning
confidence: 99%